Нейрофізіологічне підгрунтя структурної організації мовного матеріалу - Кисленко, Ю.І. (Видавничий дім "Академперіодика" НАН України, 2007)
The analysis of visual tract's neurophysiology on the structural and functional levels allows one to surely predict the peculiarities of the structure of language; i.e. the system organization of language is mostly defined by the system of perception and processing of visual data.